Review on the Reliability of Medical Contents on YouTube - Okagbue, Hilary I; Oguntunde, Pelumi E; Bishop, Sheila A; Obasi, Emmanuela C M; Opanuga, Abiodun A; Ogundile, Opeyemi P (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Abstract— Social media and YouTube, in particular, has become an avenue for quick dissemination of information. Patients now search the YouTube website for information on diseases, treatment options, surgery, and general health information. This paper reviews the different reliability methods, results, conclusions and recommendations of contributions on the medical videos on YouTube. A keyword search was done on different databases such as PubMed, Scopus, Web of Science and Google Scholar to generate articles related to the subject matter. No eligibility criteria were defined because the research is partly systematic. Descriptive statistics were used to present the information obtained from the analysis of the previously published papers in this context. The results are as follows: (i). DISCERN, JAMAS and GQS are the most frequent assessment tools used by authors in the determination of the reliability of medical videos on YouTube. (ii). 60% of the independent reviewers that assessed the reliability of the YouTube videos are often two in number. (iii). 65% of the articles concluded that medical videos on YouTube contain misleading information. (iv). User engagements for low and high-quality videos are 58% and 42% respectively. (v). 36.3 % of the total videos were uploaded by trusted sources such as medical and health professionals from recognized or prestigious hospitals, while 63.7% were uploaded by other sources whose affiliations cannot be independently verified. (vi). Out of the total 2675 medical videos assessed, 1589 (59%) are categorized as having useful contents that can influence positively on patient education while 1086 (41%) are categorized as misleading and (vii). Only 35% of the papers strongly recommended that medical videos on YouTube are useful and can be a good source of patient education. Awareness is needed to educate patients on the benefits and dangers of assessing medical videos on YouTube. Videos uploaded by authentic medical personnel or organizations are strongly recommended.